Improvement in symptoms and signs in the forefoot of patients with rheumatoid arthritis treated with anti-TNF therapy. - Bowen, C; Edwards, C; Hooper, L; Dewbury, K; Sampson, M; Sawyer, S; Burridge, J; Arden, N (2010)
BACKGROUND: Inhibition of tumour necrosis factor (TNF) is an effective way of reducing synovitis and preventing joint damage in rheumatoid arthritis (RA), yet very little is known about its specific effect on foot pain and disability. The aim of this study was to evaluate whether anti-TNF therapy alters the presence of forefoot pathology and/or reduces foot pain and disability. METHODS: Consecutive RA patients starting anti-TNF therapy (infliximab, etanercept, adalimumab) were assessed for presence of synovial hypertrophy and synovitis in the 2nd and 5th metatarso-phalangeal (MTP) joints and plantar forefoot bursal hypertrophy before and 12 weeks after therapy. Tender MTP joints and swollen bursae were established clinically by an experienced podiatrist and ultrasound (US) images were acquired and interpreted by a radiologist. Assessment of patient reported disease impact on the foot was performed using the Manchester Foot Pain and Disability Index (MFPDI). RESULTS: 31 patients (24 female, 7 male) with RA (12 seronegative, 19 seropositive) completed the study: mean age 59.6 (SD 10.1) years, disease duration 11.1 (SD 10.5) years, and previous number of Disease Modifying Anti Rheumatic Drugs 3.0 (1.6). Significant differences after therapy were found for Erythrocyte Sedimentation Rate (t = 4.014, p < 0.001), C-reactive protein (t = 3.889, p = 0.001), 28 joint Disease Activity Score (t = 3.712, p = 0.0001), Visual Analog Scale (t = 2.735, p = 0.011) and Manchester Foot Pain and Disability Index (t = 3.712, p = 0.001).Presence of MTP joint synovial hypertrophy on US was noted in 67.5% of joints at baseline and 54.8% of joints at twelve weeks. Presence of plantar forefoot bursal hypertrophy on US was noted in 83.3% of feet at baseline and 75% at twelve weeks. Although there was a trend for reduction in observed presence of person specific forefoot pathology, when the frequencies were analysed (McNemar) this was not significant. CONCLUSIONS: Significant improvements were seen in patient reported foot pain and disability 12 weeks after commencing TNF inhibition in RA, but this may not be enough time to detect changes in forefoot pathology.